Feasibility of Traditional Market Revitalization for Improving the Performance of Small Trader Performance in Sidoarjo - Susi Hariyawati; Siti Ning Farida; Lilik Nirwana (Nusantara Science and Technology Proceedings)
Traditional markets can be done by organizing and fixing traditional markets, where the weaknesses in traditional markets that cause the decline in traditional market competitiveness itself must be addressed.Based on the results of the 1st year of research the feasibility of revitalization resulted Payback period for 11.02 months, Project completion target = 20 months, If Payback Period 11.0` <20 months, then the project is feasible.Based on the observation year 1 that some traders (38%) still outside the market area are not willing to occupy the area within the market. The purpose of the second year of research is to: (1) Determine the profile of small traders of traditional markets in PasarBananganSidoarjo; (2) Analyzing the factors that influence the improvement of small trader's performance. Determination of traditional market sample using Purposive Sampling method, determining samples of traditional market traders using Simple Random Sampling method, while determining consumer sample using Acidental Sampling Observation is done to support the sampling process through coordination with related institutions, primary and secondary data collection. Descriptive statistics used for analysis of research objectives 1) and Multiple Linear Regression for goal analysis. The results showed that: Partially significant test of variable regression coefficient of Revitalization, Merchant Resources influence on merchant's performance. simultaneously Revitalization variables, Merchant Resources on Performance of merchants Revitalization, Total score of power factor,weaknesses, opportunities and threats are 1.25 total score for power factor,the total score for the weakness factor is 0.96, the total factor score is 1.69 and the total score for the threat factor is. 0.18 . After evaluated by using SWOT matrix, it is known that small trader profile of Pasar Larangan is in quadrant I with coordinate point (0.11:0.8). In this quadrant it is seen that business actors are in advanced development stage because of the opportunity and power factor that is very influential on the Performance despite the threats and weaknesses that always exist.